Performance of Winter Crops Under Eucalyptus tereticornis Based Agrisilviculture System - Kumar, A.; Nandal, C.P.S. (Indian Journal of Agroforestry, 2020)
A study was undertaken during the winter season of 2001-02 at CCS Haryana Agricultural University, Hissar to examine the production potential of winter season crops under two and a half years old eucalypts Eucalyptus tereticomis at 6 m x 2 m based agrisilviculture system. The treatments included five test crops viz., wheat (Triticum aestivum), berseem (Trifolium alexandrinum), potato (Solanum tuberosum), mustard (Brassica spp.) and lentil (Lens esculenta). In general, all the test crops sown in the interspaces of eucalypts showed reduced plant vigour interms of plant height, stem diameter, number of branches and yield attributes as compared to control. The yield of lentil, berseem, wheat, potato and mustard under eucalypts decreased to the tune of 16.3, 52.1, 62.3, 80.8 and 82.4 per cent, respectively. Lentil recorded least reduction in yield, however, from gross income point of view, wheat was found most economical crop under eucalypts.